Molecular mechanisms underlying inherited photoreceptor degeneration as targets for therapeutic intervention - Bighinati, Andrea; Adani, Elisa; Stanzani, Agnese; D’Alessandro, Sara; Marigo, Valeria (Frontiers in Cellular Neuroscience, 2024)
Retinitis Pigmentosa (RP) is a form of retinal degeneration characterized by primary degeneration of rod photoreceptors followed by a secondary cone loss that leads to vision impairment and finally blindness. This is a rare disease with mutations in several genes and high genetic heterogeneity. A challenging effort has been the characterization of the molecular mechanisms underlying photoreceptor cell death during the progression of the disease. Some of the cell death pathways have been identified and comprise stress events found in several neurodegenerative diseases such as oxidative stress, inflammation, calcium imbalance and endoplasmic reticulum stress. Other cell death mechanisms appear more relevant to photoreceptor cells, such as high levels of cGMP and metabolic changes. Here we review some of the cell death pathways characterized in the RP mutant retina and discuss preclinical studies of therapeutic approaches targeting the molecular outcomes that lead to photoreceptor cell demise.